(untitled) (Journal of Social Sciences Review, 2023)
There is a difference in the learning environment between rural and urban areas. When compared with rural areas, urban areas are always found to have better facilities with regards to learning. When it comes to academic achievements and career development, science is the most preferred field of study. Parents and students, particularly in rural areas, have developed the belief that science is the only path to a successful future career. This study explores the cognitive sciences and learning environment in rural Punjab. For this purpose, rural areas of Punjab (Sargodha, Mianwali, and Rajanpur) have been selected. The current study implies qualitative research methods, i.e., in-depth interviews. While using the purposive sampling technique, a sample size of 12 respondents (4 students, 4 parents, and 4 teachers) has been defined. Findings of the study reveal that students in rural Punjab are highly inclined to study science, but the study environment in rural Punjab is of the transmissive type. Students face challenges while studying science in a transmissive environment. According to one study, there is a need in rural Punjab for proper facilities that can help students study science in a more teacher-student friendly environment.